Formulating Nutritious Wet Noodles with Spirulina platensis: Exploring Proximate Composition, Antioxidant Activity, and Consumer Preferences - Dewi, Resti Nurmala; Panjaitan, Fenny Crista Anastasia; Sumartini, Sumartini; Putri, Nita Ariestiana (Eksergi, 2025)
The incorporation of Spirulina platensis into food products has been extensively explored. In this study, wet noodles were enriched with spirulina at three different concentrations: 1% (P1), 5% (P2) and 10% (P3). Sensory and hedonic evaluations, proximate composition and antioxidant properties were assessed. Overall, formulations P1 and P2 were significantly preferred (p < 0.05) in terms of appearance and aroma compared to the control (P0). Additionally, the texture and taste scores of spirulina-enriched wet noodles were higher (p < 0.05) than those of the control. Among all treatments, P1 emerged as the most favourable formulation (p < 0.05) for aroma, texture, and taste in the hedonic test. Moreover, the spirulina supplementation had significant effect on the protein and fat content (p < 0.05) compared to the control noodles. Furthermore, the antioxidant activity of the spirulina wet noodles increased in a dose dependent manner. The IC50 values for DPPH radical scavenging activity were 339.749 ppm for the control (P0), and 61.473 ppm, 39.965 ppm, and 27.439 ppm for P1, P2, and P3, respectively. These results suggest that fortifying wet noodles with Spirulina platensis not only improves the sensory attributes but also enhances the nutritional quality and functional value.